STUDENTS’ PERCEPTION OF THE USE OF GOOGLE CLASSROOM FOR ONLINE ENGLISH LEARNING DURING COVID-19 PANDEMIC - St. Sarah Al-Azhari; Maemuna Muhayyang; Muh. Tahir (Universitas Negeri Makassar, 2022)
This study is a qualitative case study using the descriptive qualitative method in collecting data which aims to find out (a) students’ perceptions of interactions and how their teacher teaches English using Google Classroom, (b) students’ perceptions of their feedback given in learning English using Google Classroom, (c) students’ perceptions of the assignment from learning English using Google Classroom, (d) students’ perception of teaching materials given by the teacher in learning English using Google Classroom. The participants were students of class XII MIPA 4 of SMAN 1 Mamuju for the academic year 2021/2022 as many as thirty-four students. This study used purposive sampling in selecting the participants. The result shows that (a) students’ perception of the way their teacher of teaching English using Google Classroom was negative because the teacher was less interactive in teaching; (b) there are three types of feedback given by students to the teacher, namely asking the question during the learning process, answering teacher questions and giving statements/reasons when asking permission or notifying students if they are sick; (c) there are several students perceptions on the way the teacher gives English assignments using Google Classroom, namely positive, neutral, and negative; and (d) the students perceive the teaching material provided by the teacher in learning English using Google Classroom which gives to two perceptions, namely satisfactory and unsatisfactory.